2021
DOI: 10.25259/sni_342_2021
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous versus inhalational anesthesia trial for outcome following intracranial aneurysm surgery: A prospective randomized controlled study

Abstract: Background: For maintenance of anesthesia for intracranial aneurysmal neck clipping, both intravenous and inhalational anesthetics are in vogue. We aimed to evaluate the superiority of one agent over the other for long-term neurological outcomes in these patients. Methods: This prospective assessor-blind randomized study was conducted in 106 patients of 18–65 years of age with World Federation of Neurosurgeons Grade I-II of subarachnoid hemorrhage. After written informed consent, the patients were randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Several studies have demonstrated propofol decrease ICP by reducing CBF and CBV simultaneously [ 19 , 20 ], while desflurane anesthesia dose-dependently increases ICP by promoting cerebral vasodilation [ 9 ]. However, no difference in brain relaxation among different anesthesia regimens has been demonstrated in several clinical trials [ 10 12 ]. It should be noted that these studies were not designed to investigate the effect of anesthesia regimens on brain relaxation and the routine use of mannitol may largely influence the evaluation of brain relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated propofol decrease ICP by reducing CBF and CBV simultaneously [ 19 , 20 ], while desflurane anesthesia dose-dependently increases ICP by promoting cerebral vasodilation [ 9 ]. However, no difference in brain relaxation among different anesthesia regimens has been demonstrated in several clinical trials [ 10 12 ]. It should be noted that these studies were not designed to investigate the effect of anesthesia regimens on brain relaxation and the routine use of mannitol may largely influence the evaluation of brain relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…First, we did not supplement any objective measures to evaluate brain relaxation, such as subdural pressure and cerebrospinal fluid pressure monitoring, but only a subjective evaluation by the neurosurgeons. However, the standardized 4-point scale is the most practical and accessible measurement to evaluate brain relaxation, and it has been widely applied in many clinical studies [ 10 , 16 , 26 29 ]. Second, we only enrolled patients without severe intracranial hypertension, so the results cannot be extrapolated to patients with low cerebral compliance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 However, clinical studies failed to demonstrate the neuroprotective effects of desflurane, but they did observe the hyperemic response. 17 18 These studies were conducted in supratentorial tumors and good-grade aneurysms with minimal disturbance in cerebral physiology. A retrospective study conducted in MMD also failed to find the difference in outcome using desflurane or propofol.…”
Section: Discussionmentioning
confidence: 99%
“…This may imply institutional biases regarding locally preferred techniques versus what is supported by evidence. [16][17][18][19] Reported clinical practices and their alignment with available evidence deserve some discussion. Our survey results indicate that hypothermia is not routinely used for neuroprotection, which may be due to the results of the IHAST 20 clinical trial, and is also aligned with aSAH guidelines 2 which state that induced hypothermia during This study has some limitations as well as strengths.…”
Section: Discussionmentioning
confidence: 99%